Competitive accumulation, the geographical transfer of value, and global environmental change: International Panel for Social Progress, 2018. Rethinking Society for the 21st Century. Cambridge: Cambridge University Press. Chapter 6: Markets, Finance, and Corporations: Does Capitalism Have a Future?. Issue 2 (2nd April 2020) - Campling, Liam
Abstract : This commentary on Chapter 6 on Markets, Finance, and Corporations of the International Panel for Social Progress (IPSP 2018) report makes four points. The first suggests that proposals for legal reform of the corporation require consideration of the underlying processes of capital accumulation. Second, thinking about the articulations of global value chains and the law could help better appreciate their combined role in the geographical transfer of value. The third notes the potential for the greater analytical integration of financial and corporate dynamics through the study of the financialisation of production. Finally, it argues that future work by the IPSP should examine the articulations of political economy and global environmental change, and the spaces for 'social progress' therein.